Efficient electrocatalytic CO2 reduction to ethylene using cuprous oxide derivatives - Dong, Wenfei; Fu, Dewen; Zhang, Zhifeng; Wu, Zhiqiang; Zhao, Hongjian; Liu, Wangsuo (Frontiers in Chemistry, 2024)
Copper-based materials play a vital role in the electrochemical transformation of CO2 into C2/C2+ compounds. In this study, cross-sectional octahedral Cu2O microcrystals were prepared in situ on carbon paper electrodes via electrochemical deposition. The morphology and integrity of the exposed crystal surface (111) were meticulously controlled by adjusting the deposition potential, time, and temperature. These cross-sectional octahedral Cu2O microcrystals exhibited high electrocatalytic activity for ethylene (C2H4) production through CO2 reduction. In a 0.1 M KHCO3 electrolyte, the Faradaic efficiency for C2H4 reached 42.0% at a potential of −1.376 V vs. RHE. During continuous electrolysis over 10 h, the FE (C2H4) remained stable around 40%. During electrolysis, the fully exposed (111) crystal faces of Cu2O microcrystals are reduced to Cu0, which enhances C-C coupling and could serve as the main active sites for catalyzing the conversion of CO2 to C2H4.